On Overview of Fast dissolving tablet - Achal, Chavan; chaudhary, Bharatee; Redasani, Vivek Kumar; Bhagat, Pooja; mahadik, Rutuja (Asian Journal of Pharmaceutical Research and Development, 2023)
Fast dissolving tablets emerge as one of the popular and widely accepted dosage forms, especially for paediatric patients because of incomplete development of the muscular and nervous system and a case of geriatric patients suffering from Parkinson’s disorder or hand tremors. Few solid dosage forms like capsules and tablets are present days facing the problems like difficulty in swallowing (dysphagia), resulting in many incidences of non-compliance and making the therapy ineffective. Oral dosage form and oral route is the most preferred route of administration for various drugs have limitations like first-pass metabolism, psychiatric patients, bedridden and uncooperative patients. FDTs are disintegrating or dissolve quickly in the saliva without a need of water. Fast dissolving tablets are designed to dissolve in saliva remarkably faster, within a few seconds (less than 60 seconds), and those are real fast-dissolving tablets. The convenience of administration and improved patient compliance are important in the design of oral drug delivery system which remains the preferred route of drug delivery in spite of various disadvantages. There are several technologies that are conventional or patented based on spray drying, cotton candy process, sublimation, melt granulation, direct compression freezes drying/lyophilization, phase transition process, mass extrusion, etc. have been developed for manufacturing of FDTs